Digital Assistance for Land Deed Officials (PPAT) for Effective Electronic Mortgage Reporting - Ummiati Rahmah; Sehly Sehly; Kamoru Sabitu (Jurnal Abdimas Cendekiawan Indonesia, 2025)
Digital transformation in land administration requires Land Deed Officials (PPAT) to be prepared to utilize technology optimally, particularly in the use of the Electronic Mortgage Rights (HT-el) system. However, reporting practices in the field still experience various obstacles, such as delays in receiving document correction information, high levels of input errors, and the lack of real-time monitoring of reporting status. This impacts the slow service process and low work efficiency. This community service activity was carried out to increase the capacity of partners in utilizing the PPAT Partner System as a more effective and responsive HT-el reporting tool. The implementation of the activity included preparation, socialization, technical training, field implementation assistance, and a comprehensive evaluation. The results of the activity showed a significant increase in partner capabilities, as reflected in the reduction in reporting time from 18 hours to 7 hours (61% efficiency), a decrease in the input error rate from 32% to 9% (72% error reduction), and an increase in partner satisfaction from 3.2 to 4.7 on a Likert scale. This activity has a real impact in the form of increasing the digital competence of PPAT, accelerating the service flow, and improving the quality of administration in the HT-el reporting process.